Behavioral sociology The experimental analysis of social process - "Burgess, Robert.L." (New York, 1969)
This is the first book to set out the achievements and potential of rein- forcement theory in experimental stud- ies of human social behavior. It is a collection of articles which describe the Experimental Analysis of Behavior in terms of its sociological applications and implications. The book opens with a general intro- duction by George C. Homans. The suc- ceeding seventeen chapters or selections are arranged in three parts, the first chapter in each being an integrative essay by Burgess and Bushell. The authors' essays introduce the basic theme of the section and highlight per- tinent aspects of the methods and theory underlying the experimental analysis in three contexts. Behavioral analysis is attracting a growing number of researchers who are sociologists. Twelve of the eighteen con- tributions to the collection are written by men having this background. They have found that the orientation and methodologies of the experimental analysis are well suited to the examina- tion of some very basic sociological problems. It is their work, together with the seminal experiments of some psy- chologists working in social situations, that shapes the thesis of this collection. All of the articles are based on an in- tegrated set of behavioral principles. This, in addition to the authors' inte- grative essays provides cohesiveness in the book. The assembled articles clearly illustrate the consistent use of these be- havioral principles and techniques at all levels of analysis. In the introduction for Part I, the authors define and illustrate main ele- ments of reinforcement theory and comment upon the selections following, all of which are laboratory exper- iments. Part II presents field experi-! ments. Part III contains articles on promising, but as yet untried, areas of social behavior for analysis in terms of reinforcement theory. This sequencing of Parts recapitulates the history of this bourgeoning approach to the analysis af human social behavior. From the lab- oratory analysis of worker supervision to the design of a culture, there is a unity of perspective and procedure which ought to delight students with applied interests as well as those of a more theoretical bent. Robert L. Burgess is Associate Pro- fessor of Sociology at the University of Washintgon, Seattle. Don Bushell, Jr. is Assistant Professor in the Depart- ment of Human Development at the University of Kansas, Lawrence.
Keywords: Sociology